The proto-elamite settlement an its neighbors - Mutin, Benjamin, 1978- (Oxford ; Oakville)
lvii, 442 s.
Keywords: "The site of Tepe Yahya in southeastern Iran is famous, among other important aspects, for the Proto-Elamite complex dated to around 3000 BC (Period IVC). The material culture of Period IVC is not exclusively limited to its Proto-Elamite component, but is also characterized by the presence of elements from other Middle-Asian cultural ceramic traditions. In addition to a synthesis of the Proto-Elamite period and the material assemblage at Tepe Yahya, The Proto-Elamite Settlement and Its Neighbors provides an updated review and comprehensive discussion of the Proto-Elamite sphere, its relations to Mesopotamia, and its eastern Middle Asian neighbors. This innovative book illustrates that the “multi-cultural” situation at Tepe Yahya Period IVC was present across many sites in Middle Asia and that, in addition to the Proto-Elamite sphere and the cities of Mesopotamia, Middle Asia around 3000 BC was incorporated within an interactive “multi-players” network of polities." -